Empirical model for estimating daily erythemal UV radiation in the Central European region - Petr Hlavinka; Miroslav Trnka; Daniela Semerá dová; Zdeně k Ž alud; Martin Dubrovský; Josef Eitzinger; Philipp Weihs; Stana Simic; Mario Blumthaler; Joseph Schreder (Meteorologische Zeitschrift, 2007)
Because of its biological effects, erythemal ultraviolet (UV-ERY) radiation (280-400 nm) is a significant part of solar radiation spectrum. In this study a statistical model for estimating daily UV-ERY radiation values was developed. It is based on ground measurements conducted at eight Austrian stations (from 2000 to 2002). As inputs the model requires daily global radiation, daily extraterrestrial radiation, information about the column of total ozone in the atmosphere and the altitude of a selected station. Subsequently the performance of the model was verified by an independent data set originating from measurements in Austria and Czech Republic stations. The verification showed satisfactory performance of the model: the coefficient of determination (R2) varied from 0.97 to 0.99, the root mean square error (RMSE) varied from 9.3 % to 17.7 % and the mean bias error (MBE) varied from −2.5 % to 2.0 %. In addition, the results of the model at Hradec Králové station were compared with equivalent UV-ERY data from the Solar Radiation Database (SoDa), which are available on the Internet. After successful verification, the model was implemented within the ArcInfo GIS framework in order to carry out a spatial assessment of a stratospheric ozone reduction episode. The event of July 2005 in the Czech Republic was used as a case study. On 30 July 2005 the total ozone amount dropped 12.5 % below the long-term mean, which led to UV-ERY radiation increment ranging from 214 to 391 J·m−2·day−1.